(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
The article gives data about what teacher presence is and how can we – as we are preservice teachers – acquire it so that we can deliver our speech with our confidence by strongly claiming our presence in a classroom. Moreover, it goes into in-depth details about the mistakes non-professional teachers make and presents tips so as to avoid them.